Studi Kronofarmakologi Penggunaan Ramipril pada Pasien Hipertensi di RSUD Singaparna Medika Citrautama Kabupaten Tasikmalaya - Firli Choerun Nisa; Nur Laili Dwi Hidayati; Ilham Alifiar; Vidya Febrasca Tenderly (Universitas Borneo Lestari, 2022)
Hypertension is a condition in which blood pressure rises above normal. According to the World Health Organization (WHO), approximately 40% of people aged 25 years and over were diagnosed with hypertension worldwide in 2018. Chronopharmacology is a circadian rhythm-based therapy that can be considered relevant if the risk and symptoms of the disease can change over time. The purpose of this study was to compare the effectiveness of ramipril in hypertensive patients based on differences in time of use. The time of using the drug is divided into two, namely the light zeitgeber (06.00-18.00) and the dark zeitgeber (18.00-06.00). The research method used is analytic observational using the Cross Sectional design method, prospective data collection techniques in February-May 2022 involving 23 patients (the group using the bright ramipril zeitgeber 14 patients and the dark ramipril zeitgeber 9 patients). Based on the results of the study, patients experienced a decrease in systolic 9.9 mmHg and diastolic 5 mmHg in the ramipril group that was taken on bright zt. The decrease in systolic in the dark zt group was 16.66 mmHg and diastolic was 10.56 mmHg. Based on the results of the analysis using SPSS for the use of the drug ramipril on light zeitgeber and dark zeitgeber p value = 0.062 (p > 0.05). The conclusion is that the use of the drug ramipril on light zeitgeber (morning) or dark zeitgeber (night) gives the same effectiveness.